IMPROVING LEARNING RESULTS AND STUDENT ACTIVITY ON FABLE STORY CONTENT MATERIALS USING PICTURE STORY POWERPOINT MEDIA - Alivia Risqi Fadilah; Andika Adinanda Siswoyo; Arina Artika Sari; Muh. Radhitya Wahyu Satria; Ristin Nur Halizah Putri (Citra Dharma Cindekia, 2022)
This research was conducted to improve students understanding and learning outcomes through classroom action research using picture story media in the form of power point. This research was conducted in class II SD Negeri Kesamben 02, District Kesamben Jombang with a total of 16 students consisting of 10 boys and 6 girls. This classroom action research uses the Cooperative Learning (CIRC) learning model and aims to use illustrated story media in Indonesian language learning, as an effort to improve students' understanding and learning outcomes related to the content of fables. Collecting data in this study through observation, documentation, and student learning outcomes. The data that has been collected was analyzed using qualitative and quantitative data analysis. The results of this study indicate an increase in both learning outcomes and student activity in learning. student learning outcomes showed an increase as follows: before the increase in the average grade of 75% and after the increase to 88%. Then for the percentage of students' activeness value in cycle 1 is 37.7% and in cycle 2 is 62.5%. So it can be concluded that learning Indonesian about the content of fables through picture story media in the form of power point can improve students' understanding and learning outcomes.